Single-dose fosfomycin trometamol versus 5-day cephalexin regimen for treatment of uncomplicated lower urinary tract infections in women. - Elhanan, G (1994)
A randomized study was conducted to assess the clinical and microbiological efficacies of a single 3-g dose of fosfomycin trometamol for the treatment of uncomplicated lower urinary tract infections in women compared with a 5-day regimen of cephalexin at 0.5 g four times daily. One hundred twelve women, all of whom had documented infections with bacteria sensitive to both antibiotics, were included. Fifty-eight women received fosfomycin trometamol, and 54 women received cephalexin. The two groups did not differ in age, severity, or duration of current urinary tract infection, menstrual status, sexual activity, or use of contraceptives. Ninety percent of pathogens in the fosfomycin trometamol group and 81% in the cephalexin group were Escherichia coli (the difference is not significant [NS]). A clinical evaluation at the 5-day follow-up showed that 91% of the women in each group were free of symptoms, while five women in each group were considered therapy failures and were treated by another antibiotic course. A microbiological evaluation at the 5-day follow-up showed a 91% eradication rate in the fosfomycin trometamol group and an 83% eradication rate in the cephalexin group (NS). At the 1-month follow-up, a clinical evaluation demonstrated prolonged resolution in 86 and 78%, respectively, of the participating women (NS). A microbiological evaluation at 1 month demonstrated prolonged eradication in 47 (81%) women treated with fosfomycin trometamol and in 37 (68%) women treated with cephalexin (NS). Three and six women, respectively, had relapsed. No adverse reactions were reported by the fosfomycin trometamol-treated women, while three women treated with cephalexin reported mild adverse reactions but completed the study period. Fosfomycin trometamol in a single 3-g dose is as effective as a 5-day regimen of cephalexin for the treatment of uncomplicated lower urinary tract infection in women.